McDonald's USA : a restaurant icon's potential to thrive in a global pandemic - Mukherjee, Kaushik; Chandler, Byron; Gentry, Richard (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Over the past 65 years, McDonald's has grown to become the world's largest (McDonald's, 2020a) and most recognized fast-food restaurant company. Like other restaurant businesses during the COVID-19 pandemic, McDonald's was forced to confront how to survive. This was particularly true of McDonald's U.S. Company, McDonald's USA. McDonald's as a corporation originally achieved its industry dominance by leveraging a business model that relied on consistent operations, value, franchisor control of real estate, and a world-class supply chain. Over time, particularly in the United States, Canada, and Australia, McDonald's added additional features to its operating model.These items included drive-through windows, mobile order pickup, and delivery, all of which positioned McDonald's to successfully compete in the contactless environment mandated by the COVID-19 world. However, McDonald's direct fast-food competitors have similar advantages that afford them the same ability to take market share from fast-casual and full-service restaurants. The issue for McDonald's is how to maintain this market share momentum post COVID-19 and protect that share from direct competitors. Historically, McDonald's responds to these challenges by devoting high levels of capital spending on new locations, marketing, new products, and/or remodels, all of which add debt and take time to accomplish. McDonald's must seek solutions to combat the competition that are not capital intensive.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; COVID-19 Pandemic, 2020-; Corporations -- Growth